2010
DOI: 10.4102/jsava.v81i4.152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of different transport conditions and lairage times in a Mediterranean climate in South Africa on the meat quality of commercially crossbred Large white x Landrace pigs

Abstract: Information on the effect of road transportation conditions and lairage times on the meat quality of pork under South African conditions is very sparse. In this investigation, the effects of 2 road conditions (rough road with frequent stops -A; smooth road, few stops - B) and 2 lairage holding periods (2 h and 24 h) on the physical meat quality attributes of commercially produced pigs during summer (ambient temperatures >30 °C) in the Western Cape (South Africa) were investigated. Pig meat from pigs tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…This is explained by the fact that reserves of glycogen become depleted during lairage and after a longer lairage there is a lower muscle glycogen content and consequently higher pH value of meat. As in our study, Hoffman and Fisher (2010) determined lower drip loss after longer lairage. In addition, longer lairage increased the level of skin blemishes on the carcass.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This is explained by the fact that reserves of glycogen become depleted during lairage and after a longer lairage there is a lower muscle glycogen content and consequently higher pH value of meat. As in our study, Hoffman and Fisher (2010) determined lower drip loss after longer lairage. In addition, longer lairage increased the level of skin blemishes on the carcass.…”
Section: Resultssupporting
confidence: 82%
“…Since the rate of rigor mortis is positively correlated with the content of cortisol and lactate as indicators of stress ( Warriss et al, 2003b ), a greater degree of rigor mortis after longer lairage indicated a more stressful procedure. Lairage time affected meat colour, so after longer lairage meat became darker, less red and yellow which was also observed by Nanni Costa et al (2002) and Hoffman and Fisher (2010) .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…However, road transportation especially long-distance transportation as a stressor could do much harm to the dairy industry. The economic losses due to transport stress include decreased body weight (Greer et al, 2011;Gonzalez et al, 2012), decreased milk production and changes in meat quality (Honkavaara et al, 2003;Hoffman and Fisher, 2010;Smiecinska et al, 2011) and higher incidence of diseases. Significantly higher egg production of Dicrocoelium dendriticum was observed in the feces of transported ewes (Sotiraki et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Poor pork quality as a result of pre-slaughter stress is widespread in the industry and this is of great concern (Hambrecht et al, 2004;Hoffman & Fisher, 2010). It occurs to such an extent that even stress resistant breeds are affected (Hambrecht et al, 2004;Küchenmeister et al, 2005).…”
Section: Introductionmentioning
confidence: 99%